2018
DOI: 10.1002/nau.23740
|View full text |Cite
|
Sign up to set email alerts
|

How to use the Pelvic Organ Prolapse Quantification (POP‐Q) system?

Abstract: Aims To set out the basic description of pelvic organ prolapse (POP) using the International Continence Society/International Urogynecology Association Pelvic Organ Prolapse Quantification (POP‐Q) system. Methods The basic approach to use of the POP‐Q was identified and summarized. Results Six defined points in the vagina are identified; points Aa and Ba for the anterior vagina, Ap and Bp for the posterior vagina, and C and D for the cervix/vault. Point D is not used in women who previously had a hysterectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 22 publications
0
55
0
1
Order By: Relevance
“…Before surgery, all patients underwent pelvic and renal ultrasound and urodynamic examination. Prolapse examination using the POP‐Q was performed by the operating surgeon with no blinding at baseline, 6 weeks, and 6 and 12 months. A renal ultrasound was repeated at 6 weeks postoperatively in order to detect ureteral complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before surgery, all patients underwent pelvic and renal ultrasound and urodynamic examination. Prolapse examination using the POP‐Q was performed by the operating surgeon with no blinding at baseline, 6 weeks, and 6 and 12 months. A renal ultrasound was repeated at 6 weeks postoperatively in order to detect ureteral complications.…”
Section: Methodsmentioning
confidence: 99%
“…inclusions) and six centres performed less than 30 inclusions (mean [SD] 6.7 [4.1] inclusions). The composite success rate was significantly higher in centres with the higher volume of Pelvic organ prolapse quantification evaluation at inclusion and 12 months after surgery10 …”
mentioning
confidence: 87%
“…Our study investigated the factors influencing the difference between the ECL and the MCL. Previous studies have shown good consistency in POP-Q estimations among observers [16][17][18]. In this study, all examinations were performed by the same urogynaecologist.…”
Section: Discussionmentioning
confidence: 88%
“…Prolapse assessment using the POP‐Q confirmed a significant posterior compartment bulge (Ap: −2, Bp: 0). Magnetic resonance defecography reported mild vaginal prolapse (1.7 cm), a moderate cystocele (3.2 cm), a moderate enterocele (5.7 cm), and a moderate rectocele with distal bulge (1.2 cm) along the posterior vaginal wall.…”
Section: Case Presentationmentioning
confidence: 96%